18F-FDG PET/CT Associates With Disease Activity and Clinical Recurrence of AOSD Patients - Li, Xian; Dong, Chuning; Ma, Xiaowei; Wang, Yunhua (Frontiers in Medicine, 2021)
The purpose of this study was to explore the value of 18F-FDG PET/CT in monitoring the disease activity and predicting the prognosis of the Adult-onset Still's disease (AOSD). Methods: We retrospectively reviewed the Second Xiangya Hospital’s electronic medical records of AOSD patients who underwent 18F-FDG PET/CT. PET/CT imaging and clinical information were retrospectively reviewed and analyzed. 18F-FDG uptake was assessed by measuring standard uptake value (SUV) in the spleen, liver, bone marrow, and lymph nodes. The spleen-to-liver ratio of the SUVmax (SLRmax) and SUVmean (SLRmean), the bone-to-liver ratio of the SUVmax (BLRmax), and SUVmean (BLRmean), and the lymph nodes-to-liver ratio of the SUVmax (LyLRmax) were calculated. Clinical and laboratory information were collected and evaluated for association with metabolic parameters of 18F-FDG PET/CT. The influencing factors for recurrence within 1 year were analyzed to determine the whether 18F-FDG PET/CT can predict the prognosis of AOSD patients. Results: Elevated 18F-FDG uptake could be observed in bone marrow, spleen, and lymph nodes of AOSD patients. Correlation analysis between 18F-FDG uptake of organs and laboratory examinations showed that SLRmean positively correlated with LDH, AST, ferritin, and disease activity score (r = 0.572, 0.353, 0.586, 0.382, P < 0.05). The SLRmean had the highest correlation with ferritin (r =0586, P<0.001). All metabolic parameters in spleen, including SUVmax, SUVmean, SLRmax, and SLRmean, are positively correlated with LDH level (r = 0.405, 0.539, 0.481, 0.572, P<0.05). Bone marrow SUVmax, BLRmax, and BLRmean were correlated with C-reactive protein (CRP) level (r = 0.395, 0.437, 0.469, P <0.05). Analysis of the influencing factors of recurrence within 1 year showed that the spleen SUVmax, spleen SUVmean, SLRmax, and SLRmean of the recurrence group was significantly higher than the non-recurrence group (P<0.05). The SLRmean cutoff of 1.66 with a sensitivity of 72.7% and specificity of 80.0% had the highest performance in predicting recurrence. Conclusion:The glucose metabolism of the liver, spleen, and bone marrow of AOSD patients were correlated with laboratory inflammatory indicators and disease activity score, suggesting that 18F-FDG PET/CT could be applied to evaluate disease activity. Spleen 18F-FDG uptake may be a potential biomarker for predicting outcomes of AOSD patients